Modern strategies in therapy of elderly patients with multiple myeloma - S. S. Bessmeltsev; L. V. Stelmashenko; E. V. Kariagina; N. V. Stepanova; G. N. Salogub; T. L. Shelkovskaya; T. A. Malakhova; I. A. Skorokhod; E. I. Podoltseva; N. O. Saraeva; O. I. Kovalev; A. V. Klimovich; et al. (Онкогематология, 2022)
We used the bortezomib plus dexamethasone (VD) and bortezomib plus MP (VMP) in 56 previously untreated elderly patients with multiple myeloma. The patients were 65–89 years old. For patients who received bortezomib plus MP the overall response rate was 83%. 33.3% of patients achieved complete response (near-complete response + complete response) (based on EBMT criteria). For patients who received bortezomib plus dexamethasone the overall response rate was 73%. 34.6% of patients achieved complete response. Median overall survival in patients treated with bortezomib plus dexamethasone and bortezomib plus MP has not been reached. Median event-free survival was 15 and 17 months respectively. Side effects of bortezomib were predictable and manageable. The most common adverse events reported were asthenia, neuropathy, neutropenia and anemia. Serious adverse events were rare. These results establish VMP and VD as modern strategies in therapy of elderly untreated patients with multiple myeloma. VMP and VD is highly effective and well tolerated in elderly patients (> 65 years) with newly diagnosed multiple myeloma.